PENERAPAN ILMU MANAJEMEN KEUANGAN DALAM UMKM DI KOTA SERANG: WORKSHOP DAN PEMBINAAN BERKELANJUTAN UNTUK PERTUMBUHAN BISNIS - Afriani, Raden Irna; Kartika, Rika; Khadijah, Ina; Surachman, Surachman; Romli, Ombi; Khaeruman, Khaeruman (Yayasan Education and Social Center, 2024)
This community service activity aims to increase financial literacy and financial management abilities of MSME players so they can survive and develop amidst the economic crisis. Through training and workshops, participants are equipped with basic knowledge about financial planning, recording transactions, and managing business capital. The methods used include presentation of material, simulations and interactive discussions to encourage active participation of participants. The evaluation results show a significant increase in participants' understanding and skills regarding aspects of financial management, which they hope can be applied consistently in their business operations. This activity also emphasizes the importance of ongoing mentoring to ensure effective application of the knowledge gained. With this program, MSMEs are expected to be able to face economic challenges and contribute to local economic growth